Implementasi Penggunaan Sistem Manajemen Arus Kas Berbasis Website pada UMKM Moon Cafe - Candy Candy; Alex Alex (Jurnal Nusantara Berbakti, 2025)
Effective financial management remains a significant challenge for Micro, Small, and Medium Enterprises (MSMEs), including Moon Cafe, which previously operated without a structured system for recording cash flow. The lack of such a system impeded the ability to track financial performance and business development effectively. To address this issue, a web-based cash flow management system was introduced to improve transparency, accuracy, and efficiency in documenting financial transactions. Data collection methods such as interviews, observations, and documentation were employed to identify the needs and challenges faced by the business. The implementation results showed that the web-based system streamlined the process of real-time cash flow recording, organized financial data more effectively, and generated accurate and well-structured reports. Additionally, the system enhanced operational efficiency and offered greater financial management flexibility. With improved accessibility through digital devices, Moon Cafe can monitor its financial health more effectively and make faster strategic decisions, fostering sustainable business growth.